Stochastic simulation for the inference of transcriptional control network of yeast cyclins genes - Vohradsky, Jiri (Nucleic acids research, 2012)
Cell cycle is controlled by the activity of protein family of cyclins and cyclin-dependent kinases that are periodically expressed during cell cycle and that are conserved among different species. Genome-wide location analysis found that cyclins are controlled by a small number of transcription factors that form closed network of genes controlling each other. To investigate gene expression dynamics of this network, we developed a general procedure for stochastic simulation of gene expression process. Using the binding data, we simulated gene expression of all genes of the network for all possible combinations of regulatory interactions and by statistical comparison with experimentally measured time series excluded those interactions that formed gene expression temporal profiles significantly different from the measured ones. These experiments led to a new definition of the cyclins regulatory network coherent with the binding experiments which are kinetically plausible. Level of influence of individual regulators in control of the regulated genes is defined. Simulation results indicate particular mechanism of regulatory activity of protein complexes involved in the control of cyclins.
Keywords: Saccharomyces cerevisiae; Transcription, Genetic; Gene Regulatory Networks; genetická transkripce; regulace genové exprese u hub; genové regulační sítě; Cyclin-Dependent Kinases; stochastické procesy; cyklin-dependentní kinasy; Stochastic Processes; Cyclins; cykliny; Gene Expression Regulation, Fungal